Implementasi Bimbingan Konseling Dalam Pemilihan Karir Anak-Anak Panti Asuhan - Risa Nur Fadilla; Abdurrahman Abdurrahman (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
The purpose of this research is to ascertain how children at the Al Jami'atul WashliyahPulo Brayan orphanage are influenced by career counseling advice. We can determine, based on the collected data, which programs the counselors at the orphanage used to help children from the Al Jami'atulWashliyahPulo Brayan orphanage select careers. The strategy utilized in this study is a subjective technique with a graphic methodology, information assortment procedures are helped out through interview rules, perception rules, and poll conveyance. The head of the foundation, the counselor, and the children of the Al Jami'atulWashliyahPulo Brayan orphanage were the subjects of this study. The consequences of this study got what projects were done by the shelter advisor in completing vocation directing direction in picking a profession for the offspring of the Al Jami'atulWashliyahPulo Brayan halfway house.